Trend of Critical Discourses Analysis Researches in Linguistics Journals of Sinta 1 to 4: from CDA model to Research Design - Mutakhirani Mustafa; Nirwana; Nelly Husni Laely; Emi Anggreani Masjur; Eka Pitra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The 21st century linguistic study aims to achieve various goals, and one of them is the empowerment of Critical Discourse Analysis as constructivist approach on linguistic study. This study utilized content analysis as a research method, specifically employing a document scanning approach. The articles selected for analysis were retrieved from the websites of Sinta1 to 4 in Indonesia between 2016 and 2022. To compile a list of journals indexed in the Sinta, the researchers accessed the Sinta and conducted a keyword search using "Linguistic" (Linguistic). Following these procedures, a total of 15 Indonesian linguistic journals were identified and analyzed a total of 30 articles . The objectiveof this research was to evaluate the range of Number of Publication, principles of CDA, CDAmodel, Type of Research, Type of Qualitative Data, Research Object, data collection and analysis techniques, as well as the research subjects covered in the articles published in. The findings of this study indicate an improvement in the number of publications on critical discourse analysis over the past three years. Qualitative research designs were dominant, particularly descriptive qualitative data. The most frequently targeted object of analysis was news scripts. Observations and content analysis were the commonly used instruments and dataanalysis methods. The Norman Fairclough Model and Culture were the discourse analysis model and principles of CDA employed in the research. Based on the research findings, severalrecommendations have been proposed for future studies that prioritize critical discourse analysis. These recommendations include enhancing the differentiation of research types, exploring alternative CDA models, focusing on analytical power in the study, and adopting more precise data analysis techniques.